P088 Characterization of novel humanized IL-17 mouse preclinical platforms for the efficacy evaluation of anti-human IL17 therapeutics. (March 2019) - Christodoulou-Vafeiadou, E; Ntari, L; Kranidioti, K; Denis, MC; Karagianni, N; Kollias, G
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: As the IL17/IL23 axis has proven pathogenic for many inflammatory conditions like rheumatoid arthritis, psoriasis, IBD, multiple sclerosis (MS) and others, IL17 inhibition is an attractive target for the treatment of these diseases. Indeed, biologics targeting human IL17 (hIL17) have recently proven a successful treatment for psoriasis with similar therapeutics being currently under development for this and other diseases. Objectives: To describe novel preclinical platforms based on a hIL17A transgenic mouse model for the efficacy evaluation of human therapeutics, targeting psoriasis and MS. Methods: Human IL17A transgenic mice were generated using as transgene a 170 kb genomic DNA fragment comprising hIL17A intron exon sequences flanked by extended 5' and 3' regulatory regions. These mice were further crossed with IL17AKO 1 resulting in a mouse line (TghIL17 ) that exclusively expresses hIL17A. We standardized IMQ-induced psoriasis and MOG-induced Experimental Autoimmune Encephalomyelitis (EAE) induction protocols in these mice and characterized their response to anti hIL17 treatment. Disease severity was evaluated using established clinical and histopathological scoring scales. Results: TghIL17 mice have no overt pathology, and express hIL17A upon induction. IMQ- induced psoriasis induction in TghIL17 mice resulted in the development of skin pathology characterized clinically by skin erythema, thickening and scaling and histopathologically by acanthosis, hyperkeratosis and lymphocytic infiltration. Treatment with secukinumab resulted in alleviation of both clinical and histopathological psoriasis hallmarks to levels comparable to those observed in the IL17KO mice. MOG-induced EAE in TghIL17 mice resulted in clinical symptoms comparable to the ones observed in WT mice that involved, at the peak of the disease, paraplegia with forelimb weakness or paralysis. Treatment of EAE-affected TghIL17 mice with secukinumab ameliorated the pathological findings to a level similar to the one observed in IL17KO mice. Conclusions: TghIL17 mice upon induction develop pathologies similar to WT animals demonstrating that human IL17A efficiently replaces its mouse counterpart. Using these mice with standardized IMQ-induced psoriasis and MOG-induced EAE protocols we established and validateed with commercially approved anti-hIL17 biologics, preclinical platforms that allow the efficient and reproducible evaluation of anti-hIL17 therapeutics. Reference: Nakae S, et al . Antigen-specific T cell sensitization is impaired in Il-17-deficient mice, causing suppression of allergic cellular and humoral responses. Immunity 2002. Disclosure of Interest: None declared.